CFTR mutation compromises spermatogenesis by enhancing miR-15b maturation and suppressing its regulatory target CDC25A†. Issue 1 (15th April 2019) - Chen, Yan; Li, Xiaoliang; Liao, Huijuan; Leung, Xiaotong; He, Jiabei; Wang, Xiang; Li, Fuping; Yue, Huanxun; Xu, Wenming
Abstract: MicroRNAs (miRNAs) have recently been shown to be important for spermatogenesis; both DROSHA and Dicer1 KO mice exhibit infertility due to abnormal miRNA expression. However, the roles of individual miRNAs in spermatogenesis remain elusive. Here we demonstrated that miR-15b, a member of the miR-15/16 family, is primarily expressed in testis. A miR-15b transgenic mouse model was constructed to investigate the role of miR-15b in spermatogenesis. Impaired spermatogenesis was observed in miR-15b transgenic mice, suggesting that appropriate expression of miR-15b is vital for spermatogenesis. Furthermore, we demonstrated that overexpression of miR-15b reduced CDC25A gene post-transcriptional activity by targeting the 3′-UTR region of CDC25A, thus regulating spermatogenesis. In vitro results further demonstrated that a mutation in CFTR could affect the interaction between Ago2 with Dicer1 and that Dicer1 activity regulates miR-15b expression. We extended our study to azoospermia patients and found that infertile patients have a significantly higher level of miR-15b in semen and plasma samples. Taken together, we propose that CFTR regulation of miR-15b could be involved in the post-transcriptional regulation of CDC25A in mammalian testis and that miR-15b is important for spermatogenesis. Abstract : CFTR regulation of miR-15b is involved in the post-transcriptional regulation of CDC25A in mammalian testis and that miR-15b is important for spermatogenesis